Past, present, and future of arenavirus taxonomy - Radoshitzky, Sheli R; Bào, Yīmíng; Buchmeier, Michael J; Charrel, Rémi N; Clawson, Anna N; Clegg, Christopher S; DeRisi, Joseph L; Emonet, Sébastien; Gonzalez, Jean-Paul; Kuhn, Jens H; Lukashevich, Igor S; Peters, Clarence J; et al. (Archives of virology, 2015)
Until recently, members of the monogeneric family Arenaviridae (arenaviruses) have been known to infect only muroid rodents and, in one case, possibly phyllostomid bats. The paradigm of arenaviruses exclusively infecting small mammals shifted dramatically when several groups independently published the detection and isolation of a divergent group of arenaviruses in captive alethinophidian snakes. Preliminary phylogenetic analyses suggest that these reptilian arenaviruses constitute a sister clade to mammalian arenaviruses. Here, the members of the International Committee on Taxonomy of Viruses (ICTV) Arenaviridae Study Group, together with other experts, outline the taxonomic reorganization of the family Arenaviridae to accommodate reptilian arenaviruses and other recently discovered mammalian arenaviruses and to improve compliance with the Rules of the International Code of Virus Classification and Nomenclature (ICVCN). PAirwise Sequence Comparison (PASC) of arenavirus genomes and NP amino acid pairwise distances support the modification of the present classification. As a result, the current genus Arenavirus is replaced by two genera, Mammarenavirus and Reptarenavirus, which are established to accommodate mammalian and reptilian arenaviruses, respectively, in the same family. The current species landscape among mammalian arenaviruses is upheld, with two new species added for Lunk and Merino Walk viruses and minor corrections to the spelling of some names. The published snake arenaviruses are distributed among three new separate reptarenavirus species. Finally, a non-Latinized binomial species name scheme is adopted for all arenavirus species. In addition, the current virus abbreviations have been evaluated, and some changes are introduced to unequivocally identify each virus in electronic databases, manuscripts, and oral proceedings.